Pengaruh Suplemen Pakan Terhadap Kesehatan dan Pertumbuhan Sapi Pedaging - Dwitara Wulandari Sihombing; Muhammad Aidil Ghifari; Fitra Haikal; Said M. Sajahtra; Kiagus Muhammad Zain Basriwijaya; Faoeza Hafiz Saragih (Asosiasi Riset Ilmu Tanaman Dan Hewani Indonesia, 2025)
This study aims to analyze the effect of feed supplements on the health and growth of beef cattle. The method used is a literature review, examining various relevant sources related to livestock feed and supplements. The results show that the addition of protein in feed increases the average daily gain (ADG) of cattle by 1.0-1.2 kg/day compared to cattle without supplements (0.7 kg/day). Feed supplements also proved to improve feed conversion efficiency by up to 20-25% and reduce feed costs when combined with local feed. Additionally, the provision of minerals and vitamins such as vitamin E and selenium contributes to improving cattle immunity and reproductive health. The implementation of good livestock health management, including routine administration of vitamins and deworming, is key to enhancing the productivity and health of beef cattle.